2002
DOI: 10.1073/pnas.062059899
|View full text |Cite|
|
Sign up to set email alerts
|

Wild-type and mutated presenilins 2 trigger p53-dependent apoptosis and down-regulate presenilin 1 expression in HEK293 human cells and in murine neurons

Abstract: Presenilins 1 and 2 are two homologous proteins that, when mutated, account for most early onset Alzheimer's disease. Several lines of evidence suggest that, among various functions, presenilins could modulate cell apoptotic responses. Here we establish that the overexpression of presenilin 2 (PS2) and its mutated form Asn-141-Ile-PS2 alters the viability of human embryonic kidney (HEK)293 cells as established by combined trypan blue exclusion, sodium 3′-[1-(phenylamino-carbonyl)-3,4-tetrazolium]-bis(4-methoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 51 publications
8
118
2
Order By: Relevance
“…Furthermore, primary cultured hippocampal neurons prepared from mice harboring mutant PS1 exhibit increased vulnerability to apoptosis and activated caspase (Guo et al, 1999). Several studies have shown that mutations in PS2 enhance susceptibility to cell death (Wolozin et al, 1996;Alves da Costa et al, 2002), likely via a p53-dependent mechanism (Alves da Costa et al, 2002). However, it is presently unclear whether this neuronal death is simply a direct consequence of the accumulation of neurotoxic A␤ or whether cell death also occurs because other signaling pathways are perturbed as well.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, primary cultured hippocampal neurons prepared from mice harboring mutant PS1 exhibit increased vulnerability to apoptosis and activated caspase (Guo et al, 1999). Several studies have shown that mutations in PS2 enhance susceptibility to cell death (Wolozin et al, 1996;Alves da Costa et al, 2002), likely via a p53-dependent mechanism (Alves da Costa et al, 2002). However, it is presently unclear whether this neuronal death is simply a direct consequence of the accumulation of neurotoxic A␤ or whether cell death also occurs because other signaling pathways are perturbed as well.…”
Section: Introductionmentioning
confidence: 95%
“…Cellular p53 immunoreactivity was analyzed by Western blot, using a 1:10,000 dilution of an anti-p53 mouse monoclonal antibody (Santa Cruz Biotechnology, Santa Cruz, CA) in nuclear extracts prepared as previously described for cytochrome c translocation experiments (Alves da Costa et al, 2002) while murine brain p53 was analyzed in total homogenates, using the conditions described above. The activity of p53 was measured after transient transfection of the PG13-luciferase (PG13) cDNA kindly provided by Dr. B. Vogelstein (Baltimore, MD).…”
Section: Methodsmentioning
confidence: 99%
“…6,7,11,[30][31][32][33][34] In addition, studies that included these essential control experiments often used cells expressing either a non-functional p53 mutant or a p53 protein that is inactivated by the papilloma virus E6 protein. 12,34,35 The inability, shown herein, of PFT-a to protect these cells from apoptosis might, however, be because of a competitive Figure 6 PFT-a prevents hyperphosphorylation of pRb, but does not mediate its protective effect through this tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy could perhaps be extrapolated to other neurodegenerative diseases. Thus, we previously established that presenilin 2, its mutated counterpart (48), and its C-terminal fragment (49) trigger a pro-apoptotic phenotype that could, to some extent, account for some of the neuropathological stigmata observed in Alzheimer's disease (50,51). Amazingly, in prion-related diseases we also recently showed that overexpression of PrP c led to a drastic Mdm2-regulated, p53-dependent caspase 3 activation (29).…”
Section: ␤-Synuclein Protects Neurons From Caspase 3 Activationmentioning
confidence: 99%